2008
DOI: 10.1111/j.1540-8159.2008.01169.x
|View full text |Cite
|
Sign up to set email alerts
|

Nifekalant and Disopyramide in a Patient with Short QT Syndrome: Evaluation of Pharmacological Effects and Electrophysiological Properties

Abstract: We assessed several pharmacological effects on electrocardiogram parameters and effective refractory period (ERP) in a patient with a short QT syndrome (SQTS). Pharmacological challenge tests revealed that disopyramide and selective I(kr) blocker, nifekalant normalized QT interval, and ERP of the atrial and ventricular myocardium. This study suggested that disopyramide and nifekalant should be feasible for the drug treatment of the SQTS. Moreover, QT interval was paradoxically prolonged at higher heart rates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 13 publications
1
33
0
Order By: Relevance
“…In this pilot study, administration of disopyramide proved to be equally effective as quinidine in prolonging the QT interval and restoring the ventricular ERP toward normal 53. Similarly, amiodarone also prolonged QT interval in 2 patients of SQTS with unknown genotype 41,54…”
Section: Treatment In Sqtsmentioning
confidence: 85%
“…In this pilot study, administration of disopyramide proved to be equally effective as quinidine in prolonging the QT interval and restoring the ventricular ERP toward normal 53. Similarly, amiodarone also prolonged QT interval in 2 patients of SQTS with unknown genotype 41,54…”
Section: Treatment In Sqtsmentioning
confidence: 85%
“…Case reports highlight patients in whom gene mutations have not been identified (e.g. [90,93,100]), and a recent review reported no (identified) mutations in six of eight families and two sporadic cases [15]. It seems highly likely, therefore, that in time, additional genes/gene mutations will be identified in patients/families with the SQTS.…”
Section: Discussionmentioning
confidence: 89%
“…Disopyramide was subsequently tested in a pilot study on two SQT1 patients and was found to exert beneficial effects on QT interval, rate dependence and ventricular ERP [89]. Moreover, disopyramide has also been reported to be beneficial in a patient with SQTS of unknown genotype [90]. By comparing the potency of a series of agents against WT-hERG, N588K-hERG, another attenuated-inactivation mutant S631A and a N588K-S631A double mutant, we recently demonstrated a strong correlation between the extent of attenuation of inactivation and the reduction in drug inhibitory potency [91], with an independent study providing evidence that Note that symbols do not denote plotted data-points; rather the concentration-response relations have been plotted as continuous lines, and some line types incorporate symbols to help differentiate between the different plots.…”
Section: Treatmentmentioning
confidence: 96%
“…Disopyramide has been used clinically in a pilot study to treat SQT1 (Schimpf et al, 2007). Additionally, a case study report showed the effectiveness of both nifekalant and disopyramide in a patient with SQTS (Mizobuchi et al, 2008).…”
Section: Resultsmentioning
confidence: 97%